The Incrimination of Enforced Disappearance in the Criminal Law of the Republic of Serbia - Kolaković Bojović, Milica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2017)
Armed conflicts in the former Yugoslavia had, among other things, resulted in a large number of missing persons. Detection of missing persons has been an issue of great legal, humanitarian, and political importance in the Republic of Serbia for more than two decades. In this regard, the steps that Serbia has taken on the development of normative and institutional preconditions for the investigation of enforced disappearances, but also to prevent new ones, have been recognised and acknowledged by the international community, since they resulted in discovering the truth about the large number of missing persons. Unfortunately, this process is still not finished, and the families of the missing continuously fight for their rights in accordance with the International Standards and domestic law. However, it seems that the concept of enforced disappearances outside the context of armed conflicts is still not adequately recognized in our professional community but also by the legislator whose recent attempt to harmonize the Criminal Code with the International Convention on the Protection of All Persons from Enforced Disappearances, may be regarded as a failure, since the recommendations of the UN Committee on Enforced Dissapeareances in large part not taken into account. The same stands for obligations undertaken in the National strategy for the prosecution of war crimes by the Government of the Republic of Serbia, in early 2016.